The distribution of phosphorus fractions and desorption characteristics of some soils in the moist savanna zone of West Africa - Nwoke, O.C.; Vanlauwe, Bernard; Diels, J.; Sanginga, Nteranya; Osonubi, O. (Springer, 2004)
The fractionation of soil P into various organic and inorganic pools with differing levels of bioavailability, coupled with knowledge of the P adsorption and desorption characteristics of the soils, provides insights into management strategies that enhance P availability to crops. Sequential soil P fractionation was conducted on samples from 11 soil profiles and different experimental fields selected from the derived savanna (DS) and northern Guinea savanna (NGS) zones of the West African moist savanna to assess the influence of soil characteristics and management on soil P pools. Phosphorus adsorption and desorption studies were conducted on samples from the surface horizon of the soil profiles. The total P content varied within and among the soil profiles and tended generally to decrease as depth increased. The total P content in topsoil varied from 90 to 198 mg kg 1 of which about 30% was organically bound P. The resin P fraction was generally low (mean = 5 mg kg 1, topsoil) and decreased with depth. These low resin P levels indicate low P availability. Within the DS, where the organic resource (OM) was Senna siamea residues, the effects on soil P fractions of OM and soluble P fertilizer (PF), whether sole or in combination, were site-specific. While resin P was significantly increased by OM in some sites, no significant differences were observed in others. In the NGS fields, farmyard manure (organic resource, OM) combined with PF and PF applied alone increased the inorganic P (Pi) fractions extractable with resin, bicarbonate, and NaOH by about 400% but had no significant effect on the organic P (Po) pools and the more stable Pi forms. The P sorption capacities were low, with the adsorption maximum deduced from the Langmuir equation ranging from 36 to 230 mg kg 1. The amount of P sorbed to maintain 0.2 mg l 1 in solution ranged between 0.6 and 16 mg kg 1. Phosphorus desorption with anion exchange resin differed among the soils, with the recovery of added P ranging from 17 to 66% after 96 h. On average, more of the applied P was recovered in the DS soils than in the NGS soils. Because of the relatively low sorption capacity and the relatively high percentage recovery, small additions of P to most of the soils studied might be adequate for crop growth. In essence, quantities of P fertilizer needed in these soils might be estimated based on considerations of P uptake by crops rather than on sorption characteristics.